2015
DOI: 10.1080/10889868.2014.979278
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Kerosene byAspergillus flavusUsing Statistical Experimental Designs

Abstract: The ability of different local fungal isolates to degrade kerosene in liquid medium was studied. The results showed that the percent of kerosene degradation varied among the different tested fungi and that 60-96% of kerosene was degraded after 7 days in the presence of 0.2% (v/v) of Tween 80. The absence of the surfactant led to about 28.34% decrease of biodegradation. The degradation of 2% (v/v) of kerosene by the most efficient fungus (Aspergillus flavus) was significantly influenced by the incubation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…showed less than 96% degradation. The same isolates were used to degrade kerosene and it was found that A. fl avus had the highest degrading ability (96.31%), followed by A.niger (90.33%), while the remaining fungi were with lower activities [15]. These results confi rm that the biodegradation process depend on the type of hydrocarbon, the genus, species, and may be the strain of the fungus, as well as on nutritional and fermentation conditions.…”
Section: Biodegradation Of Diesel By Fungal Isolatessupporting
confidence: 61%
See 2 more Smart Citations
“…showed less than 96% degradation. The same isolates were used to degrade kerosene and it was found that A. fl avus had the highest degrading ability (96.31%), followed by A.niger (90.33%), while the remaining fungi were with lower activities [15]. These results confi rm that the biodegradation process depend on the type of hydrocarbon, the genus, species, and may be the strain of the fungus, as well as on nutritional and fermentation conditions.…”
Section: Biodegradation Of Diesel By Fungal Isolatessupporting
confidence: 61%
“…So, A. ustus and A. alternata fi rstly degraded and assimilated the simpler fraction of alkanes and cyclic alkanes that appeared in the lower degradation % after four days, and for growth and production of hydrolyzing enzymes that enable the fungus to degrade the more complex fractions of diesel after days fi ve and six of fermentation (high degradation from 62 to 82%). It was reported that the complex aromatic fractions of hydrocarbons are more toxic to the organisms than the aliphatic fractions [15,32]. It was a) Fig.…”
Section: Time Course Biodegradation Of 1% Diesel Fuel By a Ustus Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Response surface methodology (RSM), including central composite design and Box-Behnken design (BBD), is an efficient strategic experimental technique to determine optimal conditions for a multivariable system [17,18]. To our knowledge, P-B and RSM design, the two-step statistical experiment design has been widely employed in the optimization of various processes, such as biochemistry [19], food chemistry [20],and water treatment [21]. However, there are few reports concerning the optimization of bromate sorption on anion exchange resin.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…The mean degradation percentage of spent engine oil in different species of fungi after incubation for seven days. (Ghanem, Al-Garni, & Alhomodi, 2015) Able to synthesize various types of enzymes such as lignin peroxidase, lipase, and catalase, which contributed to its capability in tolerating hydrocarbons (Gupta, 2016;Vatsyayan & Goswami, 2016) Able to produce biosurfactants (Adekunle et al, 2015;Kiran et al, 2009) Able to produce ligninolytic enzymes such as lignin peroxidase and manganese peroxidase (Ameen, Moslem, Hadi, & Al-Sabri, 2016) Six species of fungi, which produced significant reduction in spent engine oil content, were identified according to maximum query cover and highest identity percentage with lowest error value through BLAST: Penicillium simplicissimum, Aspergillus nidulans, Aspergillus niger, Trichoderma longibrachiatum, Aspergillus ustus, and Aspergillus flavus. The ability of these fungi to grow in selective media without a carbon source (BHB) confirmed their ability to utilize spent engine oil as a substrate for growth (Thenmozhi et al, 2013).…”
Section: Exhibitmentioning
confidence: 99%